Análise, projeto e implementação de um conversor com ampla faixa de tensão de entrada aplicado a iluminação de estado sólido - Lodo, Rafael Antonio (2012)
Currently research has pointed to LEDs as the technology more efficient and durable to be used in lighting, however, it requires a static converter in order to control the electrical current flowing through the LED lamp. In this context, this work present the analysis, design and implementation of a DC/DC converter with wide input voltage range called Boost-Buck Quadratic, with a active single switch and a simple control strategy, driving a LED lamp. The converter can be powered from a battery voltage (12 VDC) to the universal AC input voltage (90 to 240 VRMS). Throughout the work, will be present the qualitative analysis, quantitative analysis, a design guideline of all converter structure and experimental results obtained through a prototype with a 12 W LED lamp.